STRATEGI PENGEMBANGAN PADI ORGANIK DI KABUPATEN MINAHASA TENGGARA (DEVELOPMENT STRATEGIES OF ORGANIC RICE IN SOUTHEAST MINAHASA DISTRICT - Riana ., Rengkung; Martha Mareyke Sendow; Agnes Estephina Loho (Sam Ratulangi University, 2021)
The purpose of this study is to formulate the right strategy to develop organic rice in Molompar Dua Utara Village. This study was conducted in November 2019 to March 2020. The data collection method used was a survey method. The data used in this study was primary dan secondary data. The primary data were obtained through direct interview with 11 respondents using a questionnaire, and the secondary data was obtained from the Agriculture Department of Southeast Minahasa Regency. The result of this study shows the right strategy for the development of Agrobiz Mitraâ€™s organic rice is growth oriented strategy, including: maintaining product certification through the use of quality organic seeds and fertilizers, avoiding products from chemical contamination to maintain consumer safety. Furthermore, expanding the marketing network by holding special markets, collaborating with the Government in setting prices for organic farming products, expanding bussiness by improving brand awareness to expand marketing network. On the other hand, experienced farmer engage in the socialization of organic rice farming.Â